Are cyclin-dependent kinases 4/6 inhibitors ready for prime time in estrogen-receptor positive metastatic breast cancer? - Genta, Sofia; Mittica, Gloria; Giannone, Gaia; Ghisoni, Eleonora; Valabrega, Giorgio (Translational Cancer Research, 2017)
Endocrine therapy is the mainstay of treatment for most hormone receptor positive (HR+), human epidermal growth factor receptor 2 (HER2) negative breast cancer (BC). Patients with metastatic disease may experience long lasting clinical benefit (CB) despite the line of endocrine therapy. The major limitation of this treatment is primary and, most frequently, acquired resistance. A better understanding of endocrine resistance has resulted in the development of new targeted agents to be integrated with endocrine therapy. The addition of a cyclin-dependent kinases 4/6 (CDK4/6) inhibitor such as ribociclib (MONALEESA-2 trial) or palbociclib (PALOMA-3 trial) to endocrine treatment improved response rate (RR), and prolonged progression-free survival (PFS), but overall survival (OS) data are not yet available. Combination therapy with CDK4/6 inhibitors allows delaying conventional chemotherapy start but increases toxicities and costs. Identification and validation of biomarkers of response that could avoid unnecessary toxicities to patients are therefore essential. Ongoing and future trials will hopefully elucidate the optimal placement of CDK4/6 inhibitors in the treatment of HR+/HER2-BC.